Probing Triple Higgs Self-Coupling and Effect of Beam Polarization in Lepton Colliders - Ahmed, Ijaz; Nawaz, Ujala; Khurshid, Taimoor; Qazi, Shamona Fawad (Advances in High Energy Physics, 2022)
One of the main objectives of almost all future (lepton) colliders is to measure the self-coupling of triple Higgs in the Standard Model. By elongating the Standard Model’s scalar sector, using incipient Higgs doublet along with a quadratic (Higgs) potential can reveal many incipient features of the model and the possibility of the emergence of additional Higgs self-couplings. The self-coupling of the Higgs boson helps in reconstructing the scalar potential. The main objective of this paper is to extract Higgs self-coupling by numerically analyzing several scattering processes governed by two Higgs doublet models (2HDM). These scattering processes include various possible combinations of final states in the triple Higgs sector. The determination of production cross-section of scattering processes is carried out using two different scenarios, one with and other without polarization of incoming beam, and is extended to a center of mass energy up to s=3TeV. The computation is carried out in type-1 2HDM. Here, we consider the case of exact alignment limit (sβα=1) and masses of extra Higgs states are equal, that is, mH=mH0=mA0=mH±. This choice minimizes the oblique parameters. The decays of the final state of each process are investigated to estimate the number of events at an integrated luminosity of 1 ab−1 and 3 ab−1.